Surgical Fixation with Cannulated Screws in the Adult Femoral Neck Fractures - Güzel, İsmail; Belhan, Oktay; Altunkılıç, Tarık (My University, 2023)
Aim: Femoral neck fractures are common injuries in orthopedic practice and result in significant morbidity and mortality. They are fractures in the intra-capsule area of the proximal femur. They usually occur in the elderly patient group. However, younger age groups could also experience femoral neck fractures as a result of high-energy traumas. The aim of the present study was to compare with the literature the outcomes in adult patients for whom surgical fixation was performed after femoral neck fracture using cannulated screws in our clinic.Materials and Methods: The study included patients for whom surgical fixation was performed for femoral neck fractures using cannulated screws between August 2010 and August 2012. Fracture non-union, delayed union, avascular necrosis and arthrosis were evaluated in patients. Avascular necrosis evaluation was performed using Ficat and Arlet classification. Functional outcomes were evaluated using Harris hip score.Results: The average follow-up period of our patients was 32 months (range: 24-48 months). Follow-ups indicated that 16 patients recovered without problems, walked with a double wand starting from about the third month with respect to the bone union status and full union was achieved in an average of six months. Non-union was observed in four patients. Ficat and Arlet avascular necrosis classification showed that four patients had avascular necrosis. The average time for these patients to be admitted to surgery was seven days. Five of our patients developed superficial wound infections. Antibiotic treatment and wound care were applied to our patients. When the patients were evaluated based on Harris hip score numerical rating chart, it was found that excellent outcomes were obtained in five patients, very good results in eight patients, good results in four patients, moderate results in two patients and poor results in one patient.Conclusion: Femoral neck fractures are a common type of injury in orthopedic practice and they result in significant morbidity and mortality when treated inappropriately. In order to reduce the rate of bone non-union, avascular necrosis or other complications that could be observed in patients who underwent surgical fixation after femoral neck fractures, and appropriate and acceptable reduction of femoral neck fracture should be realized as soon as possible, and stable fixation should be achieved.
Keywords: Internal fixation; Femoral neck fractures; Garden classification; ficat- arlet classification; Harris hip score